Pengaruh Beban Kerja terhadap Kinerja Karyawan di Konveksi Sakinah Palembang - Ardelia, Shafira; Karimudin, Yos; Santati, Parama (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effect of workload on employee performance at Palembang Sakinah Convection. The research method used is a quantitative method. Data collection techniques using research questionnaires. The total population is 48 employees and the sample used in the research using the purposive sampling method is employees in the production section of 40 respondents. Data were analyzed using simple linear regression analysis. The results of the study indicate that there is a negative and significant effect of workload on employee performance at the Palembang Sakinah Convection.